(untitled) (Journal of Global Accounting, 2022)
This paper seeks to investigate the mediating effect of corporate board attributes in the relationship between earnings behaviour and firm size of selected quoted manufacturing firms in Nigeria. Ex-post facto research design was adopted and the study population comprised of quoted manufacturing firms on the Nigerian Stock Exchange (NSE). A sample of thirty-nine (39) firms were obtained via purposive sampling technique. Data of board size, non-executive directors, board structure, CEO duality, firm size and earnings quality were obtained during the period 2010- 2019 and Structural Equation Modelling was employed. The findings support for mediation of board size, board independence, and board structure on the relationship between firm size and earnings behaviour; however, partial support was found for CEO duality. The study recommends that large firm with complex activities may seek adequate representation from a large board size. Again, there is need for strengthening the board monitoring function via inclusion of a proportionate share of independent non-executive directors relative to size of the firm.